Psychological assessment using DASS-21 and association of sociodemographic variables with mental health in health-care professionals and general population during COVID-19 pandemic - Muddasir Sharief Banday; Muntaha Manzoor; Sajad Ahmad Rather; Bilal Ahmad Para (Asian Journal of Medical Sciences, 2023)
Background: Millions of people have been impacted by COVID-19 pandemic globally. COVID-19 pandemic has descended people to the realms of uncertainty and isolation which surprisingly are associated with mental distress. Depression, anxiety and stress are one of the prominent psychological factors that might have been significantly impacted by the ongoing pandemic. Aims and Objectives: The present study was conducted predominantly with the aim of assessing psychological impact by COVID-19 in health-care professionals (HCPs) as well as in general population. Materials and Methods: The present study was an observational study conducted in Sher-i-Kashmir Institute of Medical Sciences, Soura, a tertiary level teaching hospital in Union territory of Jammu and Kashmir, India. A total of 250 participants comprising both HCPs and general population were included in the study. Depression, anxiety, stress-scale-21 questionnaire, a validated instrument, was used to assess the depression, anxiety, and stress levels among the participants. Informed consent was taken individually for volunteering in the study and participants were required to fill the questionnaire as per the directed instructions. Results: Out of 250 participants, 54.8%, 68%, and 34.4% were found to have depression, anxiety, and stress, respectively. The prevalence of severe and extremely severe depression corresponded to 9.9% and 6.8% of HCPs, respectively. Severe and extremely severe anxiety existed in 14.9% and 21.1% of HCPs, respectively, followed by 7.5% and 1.2% severe stress and extremely severe stress percentages. About 11.2% and 7.9% participants in community experienced severe and extremely severe depression, respectively. Although 19.1% and 21.3% values corresponded to severe and extremely severe anxiety in community, 5% participants were found to have severe stress, and 4 % had extremely severe stress. A significant positive correlation existed between the levels of depression, anxiety, and stress. No statistically significant association was found between DAS scores and demographic variables except anxiety scores which showed a statistically significant association with HCPs especially nurses, students, and doctors. Conclusion: The findings from this study highlight high prevalence of depression, anxiety and stress experienced during COVID-19 pandemic by all participants. Anxiety in comparison to depression and stress was found to be experienced by majority of participants. Anxiety levels were prominent in nurses, students, and doctors among HCPs.